2014
DOI: 10.4103/0301-4738.128630
|View full text |Cite
|
Sign up to set email alerts
|

Long term outcomes of bilateral congenital and developmental cataracts operated in Maharashtra, India. Miraj pediatric cataract study III

Abstract: Aim:To study long term outcome of bilateral congenital and developmental cataract surgery.Subjects:258 pediatric cataract operated eyes of 129 children.Materials and Methods:Children who underwent pediatric cataract surgery in 2004-8 were traced and examined prospectively in 2010-11. Demographic and clinical factors were noted from retrospective chart readings. All children underwent visual acuity estimation and comprehensive ocular examination in a standardized manner. L. V. Prasad Child Vision Function score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 28 publications
4
28
1
Order By: Relevance
“…The bilateral congenital and developmental cataracts had BCVA of 6/18 or greater in 109 eyes (42.2%) compared with 25% in this unilateral series, whereas the bilateral ones had BCVA of 6/24 to 6/60 in 48 (18.6%) and less than 6/60 in 101 (39.1%) eyes after surgery compared with 66.7% less than 6/60 in this unilateral series. 10 The outcome of 25% of eyes with visual acuity of 6/18 or greater was comparable to results from China (25.3% of eyes The Chinese study reported that there was no difference in unilateral cataracts operated on before age 3 and those operated on after 3 years. It concluded that surgical removal and effective visual rehabilitation did not guarantee good vision in unilateral congenital and developmental cataracts.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The bilateral congenital and developmental cataracts had BCVA of 6/18 or greater in 109 eyes (42.2%) compared with 25% in this unilateral series, whereas the bilateral ones had BCVA of 6/24 to 6/60 in 48 (18.6%) and less than 6/60 in 101 (39.1%) eyes after surgery compared with 66.7% less than 6/60 in this unilateral series. 10 The outcome of 25% of eyes with visual acuity of 6/18 or greater was comparable to results from China (25.3% of eyes The Chinese study reported that there was no difference in unilateral cataracts operated on before age 3 and those operated on after 3 years. It concluded that surgical removal and effective visual rehabilitation did not guarantee good vision in unilateral congenital and developmental cataracts.…”
Section: Discussionsupporting
confidence: 81%
“…There may be a delay between diagnosis and surgery in bilateral developmental and congenital cataracts, but the resulting visual deprivation amblyopia was similar in both eyes, unlike in unilateral cases where cortical competition rendered 1 eye severely amblyopic. 10 Eyes with some vision before surgery also had better visual outcomes perhaps because their visual systems had an opportunity to develop, unlike those eyes with dense cataracts. The results were poorer compared with bilateral congenital and developmental cataracts operated on in the same setting with a 3-to 7-year follow-up.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…9 There are excellent surgical training programs in the region, but most pediatric ophthalmologists do not live or work in rural areas. Pediatric cataract surgery is generally performed by either a pediatric or general ophthalmologist 41 in 1 of 30-40 tertiary care centers. It has been noted that surgery for girls with congenital cataracts is more often performed in secondary care centers lacking the expertise of tertiary care centers.…”
Section: Results: Regional Challengesmentioning
confidence: 99%
“…42 In the setting of a clinical research study in Maharashtra, India, long-term outcomes of 258 bilateral congenital and developmental cataract surgeries in 129 children were reported with an average duration of follow-up of 4.4 years. 41 …”
Section: Results: Regional Challengesmentioning
confidence: 99%